Pengembangan Media Video Berbasis pendekatan Saintifik Berbantuan Canva Pada Materi Sistem Pencernaan Kelas V SD Negeri 1 Sambijajar - Dea Wulandari; Rohmatus Syafi’ah; Eka Yuliana Sari (Departement of Mathematics Education, 2024)
Research on the development of video media based on a scientific approach assisted by Canva was motivated by learning that focused on Student Worksheets (LKS) and there was no media on the digestive system material. This research aims to develop and describe the validation of learning media results in the form of videos. This research uses the Analysis, Design, Development, Implementation, Evaluation (ADDIE) development model. This research instrument uses a questionnaire. The validity of the video is seen from the validation results by each of the two validators (media, material, language experts), users (student responses), practitioners (teacher responses). The validation results of video learning media on the digestive system material from media experts received an average score of 90% in the